Persepsi Mahasiswa Terhadap Penggunaan Infografis Untuk Mengajar Ketrampilan Mendengarkan Bahasa Inggris Pada Siswa MTs di Tulungagung - Lutfiyah, Shelly Nur; Wahyu Nurhayati, Dwi Astuti (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to produce mind mapping infographic learning media in social studies subjects by looking at how far the response of teachers and students to the media. In its development, researchers used ten stages of research and development from Borg and Gall, including (1) Research and Information Collecting, (2) Planning, and (3) Developa ing Preliminary From Product. (4) Preliminary Field Testing, (5 ) Main Product Revision, (6 ) Main Field Testing, (7) Operational Product Revision, (8) Operational field testing/ Operational Field Trial, (9) Final Product Revision, (10) Dissemination and Implementation. The subjects of this study were social studies teachers and class VIII students at MTS Al Ghozali Panjerejo Tulungagung with data collection instruments in the form of validation questionnaires, student response questionnaires, student observations, and pre-test and post-test scores. At the level of practicality, the student’s completeness value is 70% for the level of effectiveness tested by hypothesis testing using the Paired Sample Test with the results of sig = 0.000 then the results of sig<0.005 the average result of the pre-test value 62.8 < post -itest value of 71 then the media is declared effective to be used in the learning process in order to improve student learning outcomes.